THE IMPLEMENTATION OF JIGSAW IN TEACHING NARRATIVE TEXTAT THE SECOND YEAR SMP NEGERI 2 NGADIROJO IN 2009/2010 ACADEMIC YEAR - Bintari, Andriana Kris (2010)
This study is aimed at describing the implementation jigsaw in teaching narrative text that can seen in student's speaking ability and student's achievement. The result of the study is expected to contribute the teaching learning speaking. The study was implemented in SMP N 2 Ngadirojo, especially class XIII C using an action research. The writer took 30 students as the subject of the research. The result of the study shows that the students' motivation improves. The students accepted achievement improves that can be seen from the result of post test. The students accepted and joined the Jigsaw implementation of Jigsaw because they could follow the cooperative learning principles and Jigsaw components well. ` Meanwhile, to find the significant difference between students' achievement before and after the action, the writer used group work result. The result showed that the post - test is greater than pre - test. The result of pre - test is 26,77 and the result of post - test is 70,53, so the increased of the score is 43,76. It means that there is significant difference of students' achievement before and after implementation. The students could do the post - test better than pre- test that means the implementation jigsaw in teaching narrative text is successful to improve students' motivation to learn speaking English especially in narrative text.